Supporting people with intellectual disabilities in psychological therapies for depression: A qualitative analysis of supporters' experiences. Issue 2 (28th September 2018) - Scott, Katie; Hatton, Chris; Knight, Rosie; Singer, Kevanne; Knowles, Dawn; Dagnan, Dave; Hastings, Richard P.; Appleton, Kim; Cooper, Sally‐Ann; Melville, Craig; Jones, Rob; Williams, Chris; et al.
Abstract: Background: Clinicians recommend including carers or others in a supporting role in the therapy as an important adaptation of psychological therapies for people with intellectual disabilities. This nested qualitative study from a larger trial explored supporters' experiences of supporting people with intellectual disabilities receiving behavioural activation or guided self‐help therapies for depression. Method: Twenty‐one purposively sampled supporters were interviewed. The semi‐structured interviews were subject to framework analysis, covering expectations of therapy, views of therapy sessions, relationships with therapist and participant, and perceived changes. Results: Supporters were positive about both therapies and reported both therapy‐specific and nonspecific therapeutic factors that had significant positive impacts on people's lives. Most supporters reported their involvement contributed to the interventions' effectiveness, and helped establish closer relationships to the people they were supporting. Conclusions: The presence of supporters within psychological therapies for people with intellectual disabilities can be an effective adaptation to therapies for this population.